Cyclic Brittle‐Ductile Oscillations Recorded in Exhumed High‐Pressure Continental Units: A Record of Deep Episodic Tremor and Slow Slip Events in the Northern Apennines. (17th September 2021) - Giuntoli, Francesco; Viola, Giulio
Abstract: The geological record of deep fossil seismogenesis in subduction zones is limited due to common rock overprinting during exhumation and only a few regions expose well‐preserved deeply exhumed structures. We investigated a mesoscopic contractional duplex formed at blueschist facies conditions in continental metasediments in the Northern Apennines (Italy). Field observations reveal strain partitioning within the duplex between metapelite bands, corresponding to high‐strain zones, and metaquartzarenite bands, which form low‐strain, imbricated metric horses. Dilational shear veins occur in both lithotypes and are composed of quartz and carpholite fibers defining a stretching lineation parallel to the regional SW‐NE transport direction. Geometrical, cross cutting and petrographic relationships suggest that veins formed broadly syn‐mylonitization. Thermodynamic modeling constrains the formation of the mylonitic foliation to >0.7 GPa and ∼400°C and the dilational shear veins vein to ∼1.1 GPa and 350°C. Therefore, we document a top‐to‐the‐E‐NE thrust that formed at the deepest conditions recorded by this unit of the Northern Apennines. In the thrusted continental metasediments, aqueous fluid locally released by metamorphic dehydration reactions transiently increased pore pressure, in turn triggering brittle‐ductile cyclicity. We propose that blueschist facies dilational shear veins and mylonitic foliation represent a geological record of deep episodic tremor and slow slip events. To the best of our knowledge, this is the first time that these events are genetically associated with brittle and ductile structures of a mesoscopic duplex. We suggest that these structures could be common features of the high‐pressure metamorphic units of the Apennine orogenic belt. Plain Language Summary: The rock record of deep seismic activity is scanty because subducted rocks commonly reequilibrate during exhumation enroute to the surface. The Italian Northern Apennines expose deeply subducted rocks exhumed back to the surface that still preserve deep mineralogical assemblages and structures. We studied a contractional structure (thrust) deforming metamorphosed Palaeozoic continental sediments. These rocks display evidence of coeval discontinuous and continuous deformation in the form of veins and foliation planes, respectively. By using mineralogical assemblages and thermodynamic modeling, we constrain the formation of both veins and foliation to pressure and temperature conditions of ∼1 GPa and 350°C. These results suggest depths of 30–40 km and cold geothermal gradients typical of subduction zones. We propose that episodic pulses of aqueous fluids released due to destabilization of hydrated minerals during subduction is responsible for the formation of the observed veins. We suggest that these geological structures can be regarded as a fingerprint of deep episodic tremor and slow slip events, peculiar seismic phenomena commonly indirectly documented at convergent margins by geophysical and geodetic techniques. Key Points: E‐verging thrusting at blueschist facies conditions affects the basement of the Northern Apennines and preserves brittle/ductile structures During subduction local dehydration reactions triggered transiently high pore pressure in continental metasediments at ∼1.1 GPa and 350°C Coeval carpholite dilational shear veins and mylonitic foliation can be a geological record of deep episodic tremor and slow slip events